Lanthanide Ion Resonance‐Driven Rayleigh Scattering of Nanoparticles for Dual‐Modality Interferometric Scattering Microscopy (Adv. Sci. 32/2022). Issue 32 (14th November 2022) - Ding, Lei; Shan, Xuchen; Wang, Dejiang; Liu, Baolei; Du, Ziqing; Di, Xiangjun; Chen, Chaohao; Maddahfar, Mahnaz; Zhang, Ling; Shi, Yuzhi; Reece, Peter; Halkon, Benjamin; et al.
Abstract : Interferometric Scattering Microscopy Rayleigh scattering of the nanoparticles can be engineered by doping lanthanide ions, which is based on the enhanced polarizability of the nanoparticles when the excitation wavelength matches the ion resonance frequency of the lanthanide ions. More details can be found in article number 2203354 by Baolei Liu, Chaohao Chen, Xiaoxue Xu, Fan Wang, and co‐workers.